Comparative study of pre-operative high-resolution computed tomography in middle ear cholesteatoma with per-operative findings - Ram, Birma; Gujral, Giriraj Singh; Sarkar, Krishnendu; Sharma, Pankaj (International Journal of Research in Medical Sciences, 2023)
Background: Imaging plays an important role in the management of middle ear pathology. Temporal bone imaging is challenging and involves deep understanding of the anatomy, especially in relation to high resolution computed tomography (HRCT) imaging. An HRCT scan can precisely determine the site and extension of cholesteatoma and its sac, assessing the erosion of ossicles, evaluating the facial nerve in its entire course, tegmen and sinus plate, and determining Dural, sigmoid sinus, and jugular bulb positions. Methods: This prospective descriptive study was performed from January 2018 to May 2019 in 60 patients with cholesteatoma who were referred to the Otolaryngology department of the Command Hospital Kolkata. Preoperative high-resolution temporal bone CT scans were carried out and compared with intraoperative findings. Results: Evaluation of 60 patients and their CT scans revealed excellent correlation for presence of soft tissue mass and its extent into the middle ear and mastoid, erosion of scutum, erosion of ossicular chain and tegmen plate, good correlation for facial canal dehiscence, labyrinthine fistula and sinus plate erosions. Conclusions: HRCT temporal bone is essential for anatomical determination of cholesteatoma and its complication. Careful and thorough evaluation is needed for the early diagnosis and treatment of the disease, to prevent complications and preserve hearing. The extent of disease and associated complications like facial nerve paralysis, labyrinthine fistula, and intracranial complications often will determine the aggressiveness of the surgical approach.